Expression and Role of MicroRNAs from the miR-200 Family in the Tumor Formation and Metastatic Propensity of Pancreatic Cancer - Zamira Vanessa Diaz-Riascos; Mireia M. Ginesta; Joan Fabregat; Teresa Serrano; Juli Busquets; Louis Buscail; Pierre Cordelier; Gabriel Capellá (Elsevier, 2019)
MicroRNAs from the miR-200 family are commonly associated with the inhibition of the metastatic potential of cancer cells, following inhibition of ZEB transcription factors expression and epithelial-to-mesenchymal transition. However, previous studies performed in pancreatic adenocarcinoma revealed a more complex picture challenging this canonical model. To gain better insights into the role of miR-200 family members in this disease, we analyzed the expression of miR-200a, miR-200b, miR-200c, miR-141, miR-429, and miR-205, and ZEB1, ZEB2, and CDH1 in pancreatic tumors and matching normal adjacent parenchyma and patient-derived xenografts. We found that miR-200a, miR-429, and miR-205 are frequently overexpressed in pancreatic tumors, whereas CDH1 is downregulated, and ZEB1 and ZEB2 levels remain unchanged. Furthermore, we measured a positive correlation between miR-200 family members and CDH1 expression, and a negative correlation between ZEB1 and miR-200c, miR-141, and miR-205 expression, respectively. Interestingly, we identified significant changes in expression of epithelial-to-mesenchymal transition regulators and miR-200 members in patient-derived xenografts. Lastly, functional studies revealed that miR-141 and miR-429 inhibit the tumorigenic potential of pancreatic cancer cells. Taken together, this comprehensive analysis strongly suggests that miRNAs from the miR-200 family, and in particular miR-429, may act as a tumor suppressor gene in pancreatic cancer. Keywords: pancreatic cancer, patient-derived xenograft, miR-200 family, miR-429